Mass production of SNP markers in a nonmodel passerine bird through RAD sequencing and contig mapping to the zebra finch genome. (16th July 2013) - Bourgeois, Yann X. C.; Lhuillier, Emeline; Cézard, Timothée; Bertrand, Joris A. M.; Delahaie, Boris; Cornuault, Josselin; Duval, Thomas; Bouchez, Olivier; Milá, Borja; Thébaud, Christophe
Abstract: Here, we present an adaptation of restriction‐site‐associated DNA sequencing (RAD‐seq) to the Illumina HiSeq2000 technology that we used to produce SNP markers in very large quantities at low cost per unit in the Réunion grey white‐eye ( Zosterops borbonicus ), a nonmodel passerine bird species with no reference genome. We sequenced a set of six pools of 18–25 individuals using a single sequencing lane. This allowed us to build around 600 000 contigs, among which at least 386 000 could be mapped to the zebra finch ( Taeniopygia guttata ) genome. This yielded more than 80 000 SNPs that could be mapped unambiguously and are evenly distributed across the genome. Thus, our approach provides a good illustration of the high potential of paired‐end RAD sequencing of pooled DNA samples combined with comparative assembly to the zebra finch genome to build large contigs and characterize vast numbers of informative SNPs in nonmodel passerine bird species in a very efficient and cost‐effective way.